2016
DOI: 10.1089/jamp.2015.1219
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Therapy in Adults Receiving High Flow Nasal Cannula Oxygen Therapy

Abstract: Placing nebulizers within a HFT circuit upstream from the humidification chamber may enable to deliver clinically relevant masses of aerosol at the cannula outlet, but more importantly downstream of the nose and pharynx, even in case of high patients' inspiratory flow. This method of aerosol therapy is expected to produce a bronchodilatatory effect to be evaluated in the clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
125
5
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(169 citation statements)
references
References 36 publications
25
125
5
6
Order By: Relevance
“…Sweeney et al showed that the mean tracheal dose during simulated HFNT in vitro is significantly lower for a cystic fibrosis breathing profile than for normal adult breathing [32]. Conversely, Reminiac et al reported that the respirable mass of drug was significantly higher during simulated respiratory distress than simulated quiet breathing [22]. Dailey et al showed that with a distressed breathing pattern, aerosol delivery was greater at 30 and 50 LPM than with a quiet breathing pattern [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sweeney et al showed that the mean tracheal dose during simulated HFNT in vitro is significantly lower for a cystic fibrosis breathing profile than for normal adult breathing [32]. Conversely, Reminiac et al reported that the respirable mass of drug was significantly higher during simulated respiratory distress than simulated quiet breathing [22]. Dailey et al showed that with a distressed breathing pattern, aerosol delivery was greater at 30 and 50 LPM than with a quiet breathing pattern [33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Perry et al reported that the in vitro inspired dose during HFNT decreased from 2.5% to 0.2% upon increasing the flow rate from 5 to 40 LPM [15]. Reminiac et al also showed reductions in inhaled dose with increasing gas flow rate [22].…”
Section: Influence Of Flow Rate On Emitted Dosementioning
confidence: 90%
See 1 more Smart Citation
“…beta agonists) continuously and without changing the interface [30–32, 49, 50] as during NIV. Recent studies suggest greater efficacy of vibrating mesh nebulizers over jet nebulizers [30, 31]. The former was used in association with NHF, and a jet nebulizer was used for children treated with standard oxygen, which further complicates interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that placement of nebulizers prior to humidifier can improve drug delivery distal to artificial airway in mechanically ventilated adult and pediatric patients in presence of bias flow, [4][5][6] patients receiving gas via high flow nasal cannula (HFNC), [7,8] as well as infants receiving nasal continuous positive airway pressure (nCPAP) and synchronized inspiratory positive airway pressure (Si PAP) [9]. While placement of aerosol generator at inlet of humidifier has been shown to improve aerosol delivery efficiency from range of nebulizers, it is not known whether aerosolized drug that rains out into the heated humidifier could result in undesirable drugs changes that could have undesirable effect on patient.…”
Section: Introductionmentioning
confidence: 99%